I-AREOR: An energy-balanced clustering protocol for implementing green IoT in smart cities. (October 2020) - Chithaluru, Premkumar; Al-Turjman, Fadi; Kumar, Manoj; Stephan, Thompson
Abstract: This research work adopts the idea of Internet of Things (IoT) for constructing a green wireless sensor network (WSN) for improving sensor based communication in future smart cities. To achieve green IoT implementation, it is important to take necessary measures to prevent energy depletion and promote energy efficiency techniques. Clustering can extend the lifetime of such networks and its efficiency depends on the selection of quality clustering schemes. To balance the energy consumption for maximizing the network lifetime, this paper proposes an Improved-Adaptive Ranking based Energy-efficient Opportunistic Routing protocol (I-AREOR), based on regional density, relative distance, and residual energy. Importantly, the first node death (FND), half node death (HND), and last node death (LND) are the major challenges for improving the energy efficiency. Therefore, the proposed approach provides a solution to extend the time of FND by considering the regional density, relative distance, and residual energy of the sensor nodes. I-AREOR protocol considers the energy parameters based on dynamic threshold for each round. The demonstrated results show that the I-AREOR clustering technique shows more efficiency in maximizing the network lifetime as compared to the existing algorithms.